The Theoretical Description for Fructose Fermentation Product Hydroxyquinol and its Ether Sesamol Amperometric Determination in Tahini Halva and Lokum - Volodymyr Tkach; Kushnir, Marta; Korniienko, Iryna; Larysa, Yastremska; Kuznetsova, Olena; Kryvetskyi, Viktor; Kryvetska, Inna; Kryvetskyi, Igor; Yagodynets, Petro; Kormosh, Zholt; Fedorova, Dina; Chikun, Nadiia (Orbital: The Electronic Journal of Chemistry, 2023)
For the first time, hydroxyquinol and sesamol electrochemical amperometric determination in tahini halva and lokum Turkish delights has been described. The electroanalytical process is given by amavadin-modified conducting polymer, in which both monomer and dopant may be natural compounds. Taking into account the ionic nature of the modifier, even in neutral medium the oscillatory behavior will be more probable in this system than in the simplest cases. Nevertheless, the amavadin-modified conducting polymer may be efficient electrode modifier for hydroxyquinol and sesamol electrochemical determination in Turkish delights like lokum and tahini halva.